Culture Enrichment Combined With Long-Read Sequencing Facilitates Genomic Understanding of Hadal Sediment Microbes - Wang, Huan; Wang, Meng; Fan, Shen; Lu, Jie; Lan, Yi; Li, Menggong; Li, Jiangyan; Liu, Rulong; Sun, Jin; Fang, Jiasong; Qian, Pei-Yuan; Zhang, Yu-Zhong; et al. (Frontiers in Marine Science, 2021)
Culture enrichment was developed to discover the uncharted microbial species in the environmental microbiota. Yet this strategy has not been widely used to study microbes of deep-sea environments. Here, we report the cultivation and metagenomic analysis of oceanic sediment microbiota collected from 6,477 m deep in the Mariana Trench. The sediment samples were cultured anaerobically in the laboratory for 4 months, before being subjected to full-length 16S rRNA gene sequencing using the PacBio technique and metagenome sequencing using both the Illumina and Oxford Nanopore techniques. The 16S rRNA gene analyses revealed 437 operational taxonomic units specific to the cultured microbes, despite the lower diversity of the cultured microbiota in comparison with the original. Metagenome analyses revealed the prevalence of functions related to respiration, energy production, and stress response in the cultured microbes, suggesting these functions may contribute to microbial proliferation under laboratory conditions. Binning of the assembled metagenome contigs of the cultured microbiota generated four nearly complete genomes affiliated to yet unclassified species under the genera Alcanivorax, Idiomarina, Sulfitobacter, and Erythrobacter. Excepting Alcanivorax, the other three genera were almost undetectable in the original samples and largely enriched in the cultured samples. The four genomes possessed a variety of genes for carbohydrate utilization and nitrite reduction, pointing to an ability to respire diverse carbon sources using nitrite as the final electron acceptor. Taken together, the findings suggest that a combination of culture enrichment and long-read sequencing is an ideal way to mine novel microbial species in the hadal environment, particularly species that are rare in their native environmental niches, and thus expand our understanding of the hadal microbial diversity and function.